Revisiting the Notion of Vicarious Cause: Allure, Metaphor, and Realism in Object-Oriented Ontology - Cogburn Jon; Young Niki (Open Philosophy)
We revisit the notion of vicarious causation in Graham Harman’s Object-Oriented Ontology (OOO) in order to first show that Harman has articulated two iterations of his account that are in tension with one another; one is found in his earlier paper “On Vicarious Causation,” while the other is contained in his later writings following the publication of Object-Oriented Ontology: A New Theory of Everything. This involves a critical assessment of his developing theory of metaphor in a way that encourages sympathetic revision in the service of improving his non-correlationist view of intra-objective relations.